PENGARUH EFEKTIVITAS MODAL KERJA, PERPUTARAN PIUTANG, DAN KEBIJAKAN UTANG TERHADAP RENTABILITAS EKONOMI PADA BIRO PERJALANAN WISATA, HOTEL DAN RESTORAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Made Ayu Gita Dianningrat; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
This study aims to determine and explain whether the Effectiveness of Working Capital, Accounts Receivable Turnover, and Debt Policy have an effect on Economic Profitability in travel agents, hotels and restaurants listed on the Indonesia Stock Exchange. The sample in this study were 15 travel agency companies, hotels and restaurants listed on the Indonesia Stock Exchange for the period 2016-2018 which were determined based on the purposive sampling method. The research test used multiple regression analysis. The results showed that the effectiveness of working capital had a positive effect on economic profitability. Meanwhile, accounts receivable turnover and debt policy have no effect on economic profitability. Further research can develop this research by using other variables which in theory have an influence on economic profitability.